Implementasi Pengetahuan Keagamaan Mahasiswa Sebagai Marbot - Chandra Pratama; Neni Noviza; Lena Marianti (Journal of Society Counseling, 2025)
The aim of this research is to determine the description of religious knowledge and the implementation of students' religious knowledge as marbots. This research was conducted at the Al – Muhajirin Mosque in Palembang in 2024. The type of research used in this research was a field study with a qualitative approach using descriptive methods. Interviews are a data collection tool. Current supporting methods include observation, documentation and assessment based on checklists in the form of checklists. The research subjects were 3 students as mosque administrators, 3 mosque administrators, and 3 mosque congregations. The data analysis techniques used are data reduction, data presentation, data validity, drawing conclusions, and validation. The results of this research show that the description of religious knowledge as a marbot includes 4 aspects, namely, faith, worship, morals, and muamalah. Marbot faith in this study is a strong faith that conveys correct worship, commendable morals, and useful mu'amarat. As for the implementation of religious knowledge such as imarah and riayah, namely carrying out the daily worship of a marbot which is obtained such as reciting the call to prayer, being a reserve imam, being a Friday prayer preacher and the main obligation to maintain the cleanliness and safety of the mosque during worship such as cleaning the ablution area, cleaning the floor, sweeping the floor, and cleaning the room in the mosque.